ANALISIS PERCEIVED ORGANIZATIONAL SUPPORT DAN KESESUAIAN PENEMPATAN KEJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN PASURUAN - Andriani, Prapti; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine and analyze the influence of Perceived Organizational Support (POS), job placement, and job satisfaction on employee performance, as well as the mediating role of job satisfaction at the Regional Financial and Revenue Management Agency of Pasuruan Regency. The population in this study consisted of all employees, totaling 100 individuals, who were also used as the research sample through a census method. Data analysis was conducted using the Partial Least Squares (PLS) approach with the SmartPLS 3.0 software. The results show that POS, job placement, and job satisfaction have a positive and significant effect on employee performance. Furthermore, POS and job placement also indirectly affect performance through job satisfaction as a mediating variable. These findings emphasize the importance of organizational support and accurate job placement in improving employee satisfaction and overall performance.